2014
DOI: 10.1111/adb.12216
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ethanol behavioral sensitization and midbrain dopamine neuron reactivity to ethanol

Abstract: Repeated ethanol injections lead to a sensitization of its stimulant effects in mice. Some recent results argue against a role for ventral tegmental area (VTA) dopamine neurons in ethanol behavioral sensitization. The aim of the present study was to test whether in vivo ethanol locomotor sensitization correlates with changes in either basal- or ethanol-evoked firing rates of dopamine neurons in vitro. Female Swiss mice were daily injected with 2.5 g/kg ethanol (or saline in the control group) for 7 days and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
(74 reference statements)
0
28
1
1
Order By: Relevance
“…VTA DA neurons are clearly involved in mediating the rewarding properties of EtOH in rodents, including self-administration (Rodd et al, 2004) and EtOH-seeking behaviors (Hauser et al, 2011). EtOH has been shown to increase the firing rate of these neurons in vivo (Gessa et al, 1985; Burkhardt and Adermark, 2014) and in vitro (Brodie et al, 1990; Didone et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…VTA DA neurons are clearly involved in mediating the rewarding properties of EtOH in rodents, including self-administration (Rodd et al, 2004) and EtOH-seeking behaviors (Hauser et al, 2011). EtOH has been shown to increase the firing rate of these neurons in vivo (Gessa et al, 1985; Burkhardt and Adermark, 2014) and in vitro (Brodie et al, 1990; Didone et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Didone et al have reported a significant positive correlation between sensitization of dopaminergic neuronal activity and behavioral sensitization induced by EtOH. 18) Because the process of sensitization to the effects of a drug is affected by the administered dose, dosing interval, and administration term, [19][20][21][22][23] we also examined EtOH-induced locomotor sensitization under different levels of illumination in the CPP box, the dependence of EtOH-induced associative learning on the administered dose, and differences in the sensitizing effects of continuous and intermittent EtOH administration.…”
mentioning
confidence: 99%
“…This common classification allows a simplified interpretation of results but has been frequently criticized because it may result in a loss of information and reduced statistical power, residual confounding and even spurious interactions [50,51]. For these reasons, we performed correlational analysis to avoid dichotomizing continuous variables and therefore optimizing our data, not to mention that this strategy has been successfully adopted in two very recent and relevant studies in the EIBS field [43,52]. This is, to our knowledge, the first time that this approach is used in a study on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This dual approach would eventually strengthen the accuracy of our results. The first sensitization score, hereafter mentioned as the "Delta Score" was calculated as [(locomotor activity on day 10) -(locomotor activity on day 1)] [13,41,43]. The second score, or "D10 Score", was the distance travelled during the 10th and last sensitization session [44,45].…”
Section: Eibs Proceduresmentioning
confidence: 99%